Vasculogenic mimicry score identifies the prognosis and immune landscape of lung adenocarcinoma - Yang, Weichang; Li, Zhouhua; Wang, Wenjun; Wu, Juan; Li, Jinbo; Huang, Xiaotian; Zhang, Xinyi; Ye, Xiaoqun (Frontiers in Genetics, 2023)
Abstract Background: Lung cancer has a high incidence and mortality rate worldwide. Vasculogenic mimicry (VM) is a specific modality of tumor angiogenesis that could potentially be a new target for tumor therapy. However, the role of VM in lung cancer is unclear. The purpose of this study was to explore the role of VM-related genes in assessing the prognosis and immune landscape of lung cancer. Methods: VM-related genes were obtained from previous studies, and the expression data and clinical data of lung adenocarcinoma (LUAD) patients were obtained from the TCGA database and GEO database. We performed enrichment analysis of 24 VM-related genes and screened hub genes by constructing protein–protein interaction network and using Cytoscape software. Subsequently, we developed the VM score based on univariate Cox regression analysis and Lasso analysis and validated VM score on the GSE72094 dataset. In addition, we constructed a nomogram based on VM score in the TCGA cohort. Finally, we explored the correlation between VM score and tumor microenvironment, immune cell infiltration, immune checkpoints, and drug sensitivity. Results: Enrichment analysis revealed that VM-related genes were associated with the HIF signaling pathway and angiogenic pathway. We developed VM score based on 3 genes (EPHA2, LAMC2 and LOXL2) in LUAD patients. Kaplan-Meier analysis showed that VM score was associated with poor prognosis in LUAD patients. The receiver operating characteristic curve suggested that VM score and nomogram are valid predictors for the overall survival of LUAD patients. VM score was significantly correlated with immune cell infiltration such as B cells naïve, Neutrophil, Eosinophils and there was a difference in the TME between the high VM score group and low VM score group. The high VM score group was more sensitive to antitumor drugs in LUAD patients. Conclusion: In summary, the VM score developed in this study is a valuable indicator for evaluating the prognosis and immune landscape of LUAD patients. VM may be a potential target for antitumor therapy in lung cancer.